2005
DOI: 10.1080/15287390590967360
|View full text |Cite
|
Sign up to set email alerts
|

Serum Hormones in Boys Prenatally Exposed to Polychlorinated Biphenyls and Dibenzofurans

Abstract: Polychlorinated biphenyls (PCBs) and dibenzofurans (PCDFs) are persistent environmental pollutants shown to adversely interact with several functions of the endocrine system. In 1978-1979, over 2000 Taiwanese people ingested rice oil accidentally contaminated with PCBs and PCDFs. This is one of the major toxic exposure episodes that occurred globally and was later called Yucheng (oil disease in Chinese). The children born to exposed Yucheng women were therefore exposed in utero to high doses of PCBs/PCDFs. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
3

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 47 publications
3
28
3
Order By: Relevance
“…High-level prenatal exposure to PCBs during the Yucheng incident was positively associated with estradiol but negatively associated with testosterone serum concentrations in boys at puberty (Hsu et al, 2005), whereas Mol et al (2002) reported only weak associations between serum hormone parameters at 14 years of age and the level of prenatal PCB exposure in 196 boys from a Faroese birth cohort. Hagmar et al (2001) did not find a significant correlation between serum levels of PCBs and testosterone in adult men.…”
Section: Discussionmentioning
confidence: 99%
“…High-level prenatal exposure to PCBs during the Yucheng incident was positively associated with estradiol but negatively associated with testosterone serum concentrations in boys at puberty (Hsu et al, 2005), whereas Mol et al (2002) reported only weak associations between serum hormone parameters at 14 years of age and the level of prenatal PCB exposure in 196 boys from a Faroese birth cohort. Hagmar et al (2001) did not find a significant correlation between serum levels of PCBs and testosterone in adult men.…”
Section: Discussionmentioning
confidence: 99%
“…These changes in THs were within normal reference ranges. A study of boys prenatally exposed to high doses of PCBs and polychlorinated dibenzo-p-furans (PCDFs) showed no differences in thyroid function compared with a control group (43). In conclusion, human and wildlife observations point towards subtle, but significant, effects of low-dose PCB exposure on human thyroid function.…”
Section: Introductionmentioning
confidence: 96%
“…Neither study found an association between PCB exposure and age at menarche. Last, Yang et al 104 and Hsu et al 105 described no pubertal developmental differences among boys or girls with and without exposure to PCB-and polychlorinated dibenzofuran-contaminated cooking oil.…”
Section: Human Studiesmentioning
confidence: 99%